A sea full of turtles : the search for optimism in an epoch of extinction - Streever, Bill (Pegasus Books, 2024)
"Following Bill Steever's travels under sail through Mexico's Gulf of California--the famous Sea of Cortez--we experience the region's dramatically underfunded but highly successful efforts to protect sea turtles. At the same time, Steever takes us beyond Mexico and past turtles to look at how some humans have changed their relationships with nature and how such changes may one day end the extinction crisis."--Dust jacket flap.